Parasomnias and Antidepressant Therapy: A Review of the Literature - Kierlin, Lara; Littner, Michael (Frontiers in Psychiatry, 2011)
There exists a varying level of evidence linking the use of antidepressant medication to the parasomnias, ranging from larger, more comprehensive studies in the area of RBD to primarily case reports in the NREM parasomnias. As such, practice guidelines are lacking regarding specific direction to the clinician who may be faced with a patient who has developed a parasomnia that appears to be temporally related to use of an antidepressant. In general, knowledge of the mechanisms of action of the medications, particularly with regard to the impact on sleep architecture, can provide some guidance. There is a potential for SSRIs, TCAs, and SNRIs to suppress REM, as well as the anticholinergic properties of the individual drugs to further disturb normal sleep architecture.